1997
DOI: 10.1016/s0167-2738(97)00149-5
|View full text |Cite
|
Sign up to set email alerts
|

Formation and properties of reaction layers of cobaltite electrodes on bismuth oxide electrolytes

Abstract: Interaction o f electrodes consisting o f perovskite-like rare earth elem ents (R EE) and strontium cobaltites with Bio.7 5 Yo.25Oj 5 solid electrolyte has been studied. Formation o f solid solutions L a ,_ t _ vS r ,B ivC o 0 1_ A (jc = 0 -0 .5 ; y = 0 -0 .1 ) as w ell as ( B i , _ tC or) , _ vY vO , 5 (* = 0 -0 .4 ; >' = 0 -0 .2 5 ) can occur in the diffusion layer betw een cobaltite electrodes and B i20 3-based solid electrolytes. The crystal structure, electrical conductivity and oxygen perm eability o f t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
1
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 14 publications
0
12
1
1
Order By: Relevance
“…Experimental procedures for the characterisation, including determination of the oxygen-ion transference numbers by the e.m.f. method, have been reported elsewhere (6,(9)(10)(11)(12)(13)(14). The spectroscopic analysis showed no deviations in the cation composition of the ceramics with respect to their chemical formulas within the experimental error limits; the total concentration of impurities was found to be less than 0.01 at%.…”
Section: Methodsmentioning
confidence: 60%
“…Experimental procedures for the characterisation, including determination of the oxygen-ion transference numbers by the e.m.f. method, have been reported elsewhere (6,(9)(10)(11)(12)(13)(14). The spectroscopic analysis showed no deviations in the cation composition of the ceramics with respect to their chemical formulas within the experimental error limits; the total concentration of impurities was found to be less than 0.01 at%.…”
Section: Methodsmentioning
confidence: 60%
“…1b. Kharton et al reported this reactivity is due to the formation of a solid solution by interdiffusion at the cobaltite/Bi 2 O 3 -based oxide interface [41]. Fig.…”
Section: Phase and Microstructural Analysismentioning
confidence: 97%
“…A certain shortcoming of cobalt oxide cathodes is the impossibility of using them in combination with the traditional zirconium-based electrolyte, because chemical reactions in a heated system rapidly produce La 2 Zr 2 O 7 and SrZrO 3 dielectric phases [265]. However, a combination of cobaltites and electrolytes based on bismuth and cerium oxides looks quite promising [266].…”
mentioning
confidence: 99%